Effect of combined electrostimulation and plyometric training on 30 meters dash and triple jump - Benito-Martinez, E.; Martinez-Amat, A.; Lara-Sánchez, A. J.; Berdejo-del-Fresno, D.; Martinez-Lopez, E. J. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this paper was to analyze the effects of training combining plyometrics (PT) and neuromuscular electrostimulation (ES) on speed training and triple jump. The study consisted on the application of an electrostimulation protocol and plyometric jumps to four groups of young athletes (Control, G II, G III and G IV). Methods: Eighty-four young athletes took part in the study (40 girls and 44 boys). All of them were sprinters (100 and 200 meters dash, and 100 and 110 hurdles meters), their mean age, weight and height being 15.9±1.4 years old, 58.53±8.05 kg, and 1.68±0.07 m, respectively. After 8 weeks of training, a 30-meter sprint launched test -time being measured by photoelectric cells - and a triple jump test from static position were completed. Repeated measures ANCOVA were used. Results: The only group that improved significantly in the speed test (PConclusion: The most effective training aimed at improving the speed of 30 m is simultaneous combined training. Regarding triple jump, the results showed significant improvements in the performance of athletes who used both simultaneous combined training and used ES followed by plyometrics. However, no significant improvement was observed after PT training prior to ES.